Effectiveness of denture cleansers on flexible denture base resins in the removal of stains colored by food colorant solution: An in vitro study - Gujrathi Richa; K Mahendranadh Reddy; Y Mahadev Shastry; S Venkat Aditya; P Jaya Krishna Babu (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of the study was to compare the efficiency of three denture cleansers (Valclean, Polident and Clinsodent) in removal of turmeric stains from flexible denture base resins. Settings and Design: In vitro - comparative study. Materials and Methods: A total of 45 specimens of flexible denture base resins were fabricated and subjected to baseline colour measurements using spectrophotometer. Specimens were stained with turmeric and colour measurements of stained specimens were made. All the stained specimens were divided into three groups (n = 15) for removal of stains with three denture cleansers: Valclean, Polident, Clinsodent and colour measurements of cleansed specimens were made. The colour measurements (ΔE) values obtained were collected and statistical analysis was done. Statistical Analysis Used: One-way ANOVA (Analysis of Variance), Tukey's post hoc test. Results: One way ANOVA test revealed that the mean colour difference of three groups were statistically different with P value < 0.001. A further Tukey post hoc test revealed that the Valclean group had lesser mean scores than Polident and Clinsodent group. Conclusion: It was concluded that Valclean showed statistically significant greater stain removal efficiency than Polident followed by Clinsodent.